The influence of psychological needs and motivation on game cheating: insights from self-determination theory - Lee, Sung Je; Jeong, Eui Jun; Kim, Dan J.; Kong, Jeonyoung (Frontiers in Psychology, 2023)
Game cheating (i.e. behavior of violating rules in games by using unregulated software or assistive devices to gain advantage) poses a fatal problem as it destroys fair competition systems and negatively impacts the game ecosystem. Game cheating is reported to be common in competitive online games because they stimulate strongly a user's motivation and psychological needs. However, there is still in lack of academic research which focused on the issue from the psycho-social perspective. This study investigated the relationships between basic psychological needs (i.e., autonomy, competence, and relatedness) and motivation (i.e., intrinsic and extrinsic) based on selfdetermination theory, and examined their effects on the degree of game cheating with survey data of 322 gamers in a competitive online gaming community. The results showed the opposite associations between the two forms of motivation (intrinsic and extrinsic) and game cheating. On one hand, extrinsic motivation decreased by autonomy enhanced the degree of game cheating. On the other hand, intrinsic motivation increased by both autonomy and relatedness finally abated game cheating. Competence did not influence any form of motivation. The results indicated that people motivated by interest or enjoyment (i.e., intrinsic motivation) of the game tend to view game cheating negatively while those motivated by game victory and rewards are likely to have positive attitudes toward game cheating. Increasing the degree of user autonomy and social relations in the game could decrease game cheating through the enhancement of intrinsic motivation. The theoretical and practical implications of the results were discussed.